2019
DOI: 10.3390/coatings9070422
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Multiple Laser Scanning and Conventional Techniques on Zirconia Shear Bond Strength

Abstract: This study aimed to compare the impact of different laser scanning with that of conventional methods on zirconia surface treatment through evaluation of shear bond strength (SBS) values. One hundred and thirty-two sintered zirconia cubic-samples were prepared and randomly divided into six study groups: milling control (without surface treatment); grinding; sandblasting; and three-times, four-times, and five-times laser scanning groups. The treatment process for the first three groups was performed before the z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Results showed that 5.25% NaClO had an acceptable deproteinization effect. The removal of the proteins by chemical means had no major effect on the elastic modulus and hardness of the dental enamel [ 35 ], as well as the laser surface treatments on the SBS between zirconia and veneering ceramic [ 36 , 37 ]. In recent years, studies have been conducted on the application of CO 2 laser pretreatment of the enamel surface to prevent enamel demineralization owing to acid erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that 5.25% NaClO had an acceptable deproteinization effect. The removal of the proteins by chemical means had no major effect on the elastic modulus and hardness of the dental enamel [ 35 ], as well as the laser surface treatments on the SBS between zirconia and veneering ceramic [ 36 , 37 ]. In recent years, studies have been conducted on the application of CO 2 laser pretreatment of the enamel surface to prevent enamel demineralization owing to acid erosion.…”
Section: Discussionmentioning
confidence: 99%
“…The asreceived TZ-3Y-E powder shows mixture of monoclinic and tetragonal phases assembley according to XRD difraction peaks in Figure 4. The most XRD diffraction can be indexed using T phase data sheet (XRD PDF#82-1241), and diffraction peaks [11] from M phase [11] are also visible as per XRD PDF card (XRD PDF#86-1449). The mixtures phase of the as- received powder can possibly be attributed to the inhomogious distribution of Y in 3Y-TZP nano powders [5].…”
Section: Resultsmentioning
confidence: 99%
“…Silicon dioxide (SiO 2 ) is a common modification layer given its superior physicochemical stability and biocompatibility. Importantly, the oxide layer may obstruct ion movement and release, improving metal mechanical properties and stability [11].…”
Section: Introductionmentioning
confidence: 99%